Metal-chelating properties, electrochemical behavior, scavenging and cytoprotective activities of six natural phenolics - Psotova, Jitka; Lasovsky, Jan; Vicar, Jaroslav (Biomedical papers, 2003)
Chelation, electrochemical, antioxidant and cytoprotective properties of six phenolics - cynarin and caffeic, chlorogenic, ferulic, protocatechuic and rosmarinic acids were studied on the following models: (i) chelation of transition metals, (ii) quenching of the diphenylpicrylhydrazyl radical (DPPH), (iii) determination of half-wave potential, (iv) erythrocytres or mitochondrial membranes damaged by tert-butyl hydroperoxide (tBH) and (v) a primary culture of rat hepatocytes intoxicated by Cu(II) and Fe(III) or tBH. All phenolics suppressed cell membrane damage induced by transition metals or tBH. The protectivity correlated with their capacity to bind transition metals, to scavenge DPPH radical and with the value of half-wave potentials. In in vitro assays, the most promising was rosmarinic acid.
Keywords: Phenolic acids / Chelatation / DPPH / Cyclic voltammetry / Lipid peroxidation / Rat mitochondria / Rat erythrocytes / Rat hepatocytes